Akbar's History of the Timurids. Issue 2 (3rd July 2021) - Melville, Charles
ABSTRACT: In around 1584, while based in his capital at Fatehpur-Sikri, Akbar commissioned a history of Timur and his successors, including his own reign up to that date. The result, the Tarikh-i Khandan-i Timuriyya, an impressively large and heavily illustrated manuscript, now preserved in Patna, with 132 full-page paintings on 332 folios, has not received the same level of attention as Akbar's other historical commissions from around the same period, notably the Tarikh-i Alfi and the Baburnama . In particular, little or no attention has been paid to the text. This paper seeks to put the manuscript both in its immediate historical and historiographical context and in its relationship with these other illustrated works, created to celebrate Akbar's political and spiritual authority and dynastic inheritance. It can be shown that the portion of the Tarikh-i Alfi that covers the same period – including the reigns of Babur, Humayun and Akbar – draws almost verbatim on the Khandan-i Timuriyya . This suggests that the same author might have been responsible for both works and is consistent with other indications that the production of the manuscript might have been later than generally supposed.